BALL MECHANISMS USED IN METAL CUTTING MACHINES - Kenjaboev Sh.Sh.; Abelkasimova M (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article contains information about the ball mechanisms used in metal cutting machines, their structure, kinematic schemes and principles of operation.